SISTEM OPTIK INTERFEROMETER MICHELSON MENGGUNAKAN DUA SUMBER LASER UNTUK MEMPEROLEH POLA FRINJI - Yayuk Widamarti; Minarni '; Maksi Ginting (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Wavemeter could be built using an interferometer with two laser sources. In this study, Michelson interferometer was built using two lasers which were He-Ne laser and diode laser. Characteristics of its fringe pattern were analyzed based on the laser power and beam size. The results showed that fringe pattern for laser He-Ne was obtained at arm length 12.5 cm x 12.5 cm with the beam height from optical table of 11.7 cm. He-Ne laser used was 632.8 nm in wavelength with the 5 mW power made by Meredith instrument. The diode laser had wavelength 650 nm with the power of 5 mW made byRoithner. The output of He-Ne laser from the interferometer system had 0.3 mW, diode laser by 0.5 mW. The best fringe pattern for both lasers was with visibilities rangedfrom 0.63 and 0.098, and beam width of each laser of 4.11 mm for He-Ne laser and 4.30 mm x 4.26 mm for diode laser.